Isolation and characterization of heparin and gelatin binding stallion seminal plasma proteins - ARANGASAMY, A; BHURE, S K; DWIVEDI, S K (The Indian Journal of Animal Sciences, 2011)
Selnen ejaculates (12) were obtained from 3 Adult :Nlarwari stallions and were subjected to plaslna separation im.mediately after collection by centrifugation at 2000 rpm for 20 min and stored in -20oe until analysis. In the selninal plasma the total protein concentration were estimated and the heparin and gelatin binding (HB and GB) proteins were isolated using heparin and gelatin affinity column chromatography. The molecular weight of individual isolated HB and GB protein was deternlined by SDS-PAGE analysis. The overall mean values of total protein were recorded as 28.7Â±O.7 mg/ml. Thirteen total protein bands were observed in the range of 17-95 kDa. FiveHB proteins were isolated in the range of 17-83 kDa. Four GB proteins were isolated in the range of 18-83 kDa in the stallion setninal plasma. It can be concluded that among the total proteins, 5 and 4 protein bands are having the affinity to bound with the heparin and gelatin - agarose affinity column chromatography.Â